Improving creative thinking skills through a mind map - Wida Wulandari (Global Econedu, 2025)
Students must possess 21st-century talents in order to learn efficiently. The goals of the study were to determine the effect of using the mind-mapping learning model on improving students' creative thinking abilities, as well as the average difference in creative thinking abilities between students who used the mind-mapping learning model and students who used the conventional learning model. SPSS version 24 was used to analyze the research data. The hypothesis was evaluated using the Wilcoxon and Mann-Whitney U tests. The results showed that, while using the mind-mapping learning model influenced students' creative thinking abilities, using traditional learning models had little effect on students' abilities. Pupils who use the mind-mapping learning model have higher average creative thinking power than those who use standard learning models.